Fluctuations of regional scale atmospheric features in relation to monsoon activities - PAUL, D. K.; MUJUMDAR, V. R.; PURANIK, P.V.; GHANEKAR, S. P.; DESHPANDE , V. R.; SIKKA, D. R. (MAUSAM, 1990)
The paper examines the fluctuations of some features of the regional monsoon circulation in relation to extreme activities of monsoon for the years 1979 and 1987 (bad monsoon) and 1983 and 1988 (good monsoon). The analysis indicates that some of the meteorological features fluctuated on two preferred time scales, viz., 30.50 days and 10-20 days during the four seasons.